Physical science - Ungson, Olivia B. (Quezon City : Trinitas Publishing, Inc., 2016)
Until the era of Galileo and Newton, people generally regarded Heaven and Earth as two separate entities. The recognition that we are intertwined with the rest of the universe is quite modern-scientist are still learning how tightly life down here is linked with what is going on up there.
Includes Glossary and Bibliography
English text.
Keywords: Physical science